Behavior of Hardness in Heat-treated Multi-alloyed White Cast Irons with Varying Mo Content: doi: 10.14456/mijet.2018.2 - Inthidech, Sudsakorn; Khoatepome, Paiboon (Engineering Access, 2018)
In this work, the effect of molybdenum (Mo) content on behavior of hardness in heat-treated multi-alloyed white cast iron with varying Mo content from 0 to 7.60 wt% was investigated. The cast irons were prepared under the basic alloy composition of 5 wt% Cr, W and V each. After annealing at 1223K for 18 ks, the test specimens were austenitized at 1323K for 3.6 ks in a vacuum furnace and subsequently hardened by a jet-spray of liquid nitrogen. The tempering was carried out at temperatures from 673 to 873K at 50K intervals for 12 ks. It was found that the hardness in the as-hardened state was increased progressively with an increase in the Mo content. In the tempered state, the hardness curve showed clear secondary hardening due to the precipitation of fine secondary carbides and a reduction of the retained austenite. The maximum tempered hardness (HTmax) was obtained in the specimen tempered at 798K in all specimens. The HTmax increased first, and then subsequently decreased with an increase in the Mo content. The highest HTmax value, 910 HV30, was obtained in the specimen with 5wt% Mo.